Research on computing offloading method for maritime observation monitoring sensor network - Xin SU; Haoyang XUE; Yiqing ZHOU; Jinxiu ZHU (Tongxin xuebao)
Considering the differences in computing capacity and communication resources of the maritime network nodes, a maritime network connectivity probability based method was proposed for selecting edge computing service nodes.Because of the different node densities in the near-shore and far-shore scenarios, two offloading models were established accordingly.In the near-shore scenario, a multi-node cooperative offloading method was proposed by using the genetic algorithm based on maritime multi-node cooperative offloading.In the far-shore scenario, a fault-tolerant offloading method was proposed based on the particle swarm algorithm with grouping cross learning.Simulation results show that compared with conventional methods, the proposed methods save over 30% network delay and reduces about 20% network costs, which can greatly enhance the maritime user experiences.